Behavioral evidence that select carbohydrate stimuli activate T1R-independent receptor mechanisms. (1st March 2018) - Spector, Alan C.; Schier, Lindsey A.
Abstract: Three decades ago Tony Sclafani proposed the existence of a polysaccharide taste quality that was distinguishable from the taste generated by common sweeteners and that it was mediated by a separate receptor mechanism. Since that time, evidence has accumulated, including psychophysical studies conducted in our laboratory, buttressing this hypothesis. The use of knockout (KO) mice that lack functional T1R2 + T1R3 heterodimers, the principal taste receptor for sugars and other sweeteners, have been especially informative in this regard. Such KO mice display severely diminished electrophysiological and behavioral responsiveness to sugars, artificial sweeteners, and some amino acids, yet display only slightly impaired concentration-dependent responsiveness to a representative polysaccharide, Polycose. Moreover, although results from gene deletion experiments in the literature provide strong support for the primacy of the T1R2 + T1R3 heterodimer in the taste transduction of sugars and other sweeteners, there is also growing evidence suggesting that there may be T1R-independent receptor mechanism(s) activated by select sugars, especially glucose. The output of these latter receptor mechanisms appears to be channeled into brain circuits subserving various taste functions such as cephalic phase responses and ingestive motivation. This paper highlights some of the findings from our laboratory and others that lend support for this view, while emphasizing the importance of considering the multidimensional nature of taste function in the interpretation of outcomes from experiments involving manipulations of the gustatory system.